LSD1 Promotes Bladder Cancer Progression by Upregulating LEF1 and Enhancing EMT - Xie, Qiubo; Tang, Tang; Pang, Jian; Xu, Jing; Yang, Xingxia; Wang, Linang; Huang, Yiqiang; Huang, Zhuowei; Liu, Gaolei; Tong, Dali; Zhang, Yao; Wang, Luofu; et al. (Frontiers in Oncology, 2020)
Epithelial-to-mesenchymal transition (EMT) is one of the important underlying molecular mechanisms for most types of cancers including bladder cancer. The precise underlying molecular mechanism in EMT-mediated bladder cancer progression is far from completed. LSD1, a histone lysine-specific demethylase, is known to promote cancer cell proliferation, metastasis, and chemoresistance. We found in this study that LSD1 is highly upregulated in bladder cancer specimens, especially those underwent chemotherapy, and the elevated levels of LSD1 are highly associated with bladder cancer grades, metastasis status, and prognosis. Inhibiting or knockdown LSD1 repressed not only EMT process but also cancer progression. Mechanistically, LSD1 complexes with β-catenin to transcriptionally upregulate LEF1 and subsequently enhances EMT-mediated cancer progression. More importantly, LSD1 specific inhibitor GSK2879552 is capable of repressing tumor progression in patient-derived tumor xenograft. These findings altogether suggest that LSD1 can serve as not only a prognostic biomarker but also a promising therapeutic target in bladder cancer treatment.